Doing weeknotes - What weeknotes are, how weeknotes work, and how to s tart writing weeknotes of your own - Turnbull, Giles (Use the Human Voice, 2024)
Doing weeknotes brings together various things I’ve written about week notes in different places. This text expands on things I wrote in The agile comms handbook, as well as various blog posts. Quite a lot of it is brand new. - Weeknotes for beginners - Why write weeknotes - The w eeknotes rules - Weeknotes within the corporate environment - What wee knotes can bring about - Examples of good weeknotes - How to write wee knotes - Weeknotes tips and tricks - Further reading